2017
DOI: 10.1016/j.jpsychores.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic prostatitis and comorbid non-urological overlapping pain conditions: A co-twin control study

Abstract: Objectives Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is characterized by pain and voiding symptoms in the absence of an obvious infection or other cause. CP/CPPS frequently occurs with non-urological chronic overlapping pain conditions (COPCs) of unknown etiology. We conducted a co-twin control study in men discordant for chronic prostatitis (CP), an overarching diagnosis of which approximately 90% is CP/CPPS. The primary aim was to investigate the contribution of familial factors, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Twin studies have indicated that chronic pain conditions show a heritability between 16-50% 8 . Shared heritability between pelvic pain and facial pain, and between widespread pain and abdominal pain have been reported 9,10 . Candidate gene studies have suggested that the same genetic variants are associated with multiple pain conditions, which implicated a possible shared genetic basis 11 .…”
mentioning
confidence: 99%
“…Twin studies have indicated that chronic pain conditions show a heritability between 16-50% 8 . Shared heritability between pelvic pain and facial pain, and between widespread pain and abdominal pain have been reported 9,10 . Candidate gene studies have suggested that the same genetic variants are associated with multiple pain conditions, which implicated a possible shared genetic basis 11 .…”
mentioning
confidence: 99%
“…While the overlap between some conditions is well documented in the literature, such as neck pain, headache, low back pain, and jaw/face pain, 11 few data are presented on the relationship between burning mouth syndrome (BMS) and urologic chronic pelvic pain syndrome (UCPPS), a clinical syndrome characterized, principally, by the presence of pain and discomfort in the pelvic, genital, and perineal region, associated with urinary and sexual disfunction in the absence of a diagnosable cause 12 . This condition, which encompasses both interstitial cystitis/bladder pain syndrome (IC/BPS) 13 and chronic prostatitis/chronic pelvic pain syndrome (CP/CPSS), 14 is frequently associated with irritable bowel syndrome, chronic fatigue syndrome, TMDs, vulvodynia, and fibromyalgia 15‐17 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic pelvic pain (CPP), classically defined as pain of long duration in the region of the pelvis below the umbilicus, is a debilitating condition that has a major impact on quality of life for both women and men. [1][2][3] Worldwide health care costs associated with CPP create a significant burden to society and appear to be increasing. [4][5][6] The costs of CPP may be growing because the conditions that cause CPP are commonly multifactorial and the parameters for defining the population are poorly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pelvic pain (CPP), classically defined as pain of long duration in the region of the pelvis below the umbilicus, is a debilitating condition that has a major impact on quality of life for both women and men . Worldwide health care costs associated with CPP create a significant burden to society and appear to be increasing .…”
Section: Introductionmentioning
confidence: 99%